1998
DOI: 10.1002/(sici)1096-9861(19981207)402:1<93::aid-cne7>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Efferent and collateral organization of paratrigeminal nucleus projections: An anterograde and retrograde fluorescent tracer study in the rat

Abstract: The paratrigeminal nucleus (PTN) receives primary visceral afferent projections through cranial nerves IX and X and somatic afferent projections through cranial nerve V and dorsal roots as far caudally as C7. Pressure injections of the anterograde tracer tetramethylrhodamine dextran into the PTN in the rat resulted in bilateral labeling in the nucleus of the tractus solitarius, dorsal motor nucleus of the vagus nerve, and parabrachial nucleus. Anterograde labeling in the parabrachial nucleus was strongest in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(16 citation statements)
references
References 82 publications
1
15
0
Order By: Relevance
“…Besides the NTS, a major input to the PBvl originates from the paratrigeminal nucleus (Feil and Herbert, 1995), which is a medullary cell group that receives primary afferent inputs from the pharynx, larynx, and trigeminal nerve (Saxon and Hopkins, 1998, 2006), and since the paratrigeminal nucleus is mainly involved in oral cavity and upper airway functions, this could explanation why we did not see Fos-activation in this region after blood pressure manipulations.…”
Section: Discussionmentioning
confidence: 92%
“…Besides the NTS, a major input to the PBvl originates from the paratrigeminal nucleus (Feil and Herbert, 1995), which is a medullary cell group that receives primary afferent inputs from the pharynx, larynx, and trigeminal nerve (Saxon and Hopkins, 1998, 2006), and since the paratrigeminal nucleus is mainly involved in oral cavity and upper airway functions, this could explanation why we did not see Fos-activation in this region after blood pressure manipulations.…”
Section: Discussionmentioning
confidence: 92%
“…Scattered smaller neurons (long axes around 20 μm), with relatively simple dendritic fields, were found within the spinal trigeminal tract (SpTT) itself (Cells 1 and 2). These may lie within the paratrigeminal nuclei (Saxon and Hopkins, 1998). Within the nucleus proper, the somata size varied considerably (long axes = 13–46 μm).…”
Section: Resultsmentioning
confidence: 99%
“…The afferent and efferent organization of the dPa5 region differs considerably from the vl-Vi/Vc transition in that it receives direct sensory input from trigeminal, upper cervical and vagus nerve fibers and projects to multiple medullary and pontine regions that control autonomic outflow including the NTS and CVLM (Menetrey and Basbaum 1987; Saxon and Hopkins 1998; Caous et al 2001). Similar to the response at caudal Vc, TMJ-evoked Fos-LI at the dPa5 increased with greater stimulus intensity, was mainly ipsilateral to the stimulus and was enhanced by high estrogen conditions (Bereiter 2001; Okamoto et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Lesion of the dPa5 prevented cardiovascular reflex responses to noxious stimuli (Yu et al 2002), while recording studies found that dPa5 neurons encoded facial skin stimulus intensity and became sensitized after TMJ injury (Yamazaki et al 2008). Although the dPa5 likely is critical for somatic autonomic integration in the trigeminal system (Saxon and Hopkins 1998; Caous et al 2001), these studies were performed in male animals, and thus, it is not known if sex differences influence the contribution of dPa5 to TMJ nociceptive processing.…”
Section: Discussionmentioning
confidence: 99%